The analyses and evaluation of the health condition of forest stands in the Szigetköz on the basis of infrared aerial orthophotos - Illés, Gábor; Somogyi, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2005)
The paper deals with the application of infrared orthophotos for forestry monitoring purposes. Orthophotos taken in 1991 and 1999 of the floodplain of the Danube in the Szigetköz were used for supervised automatic classification on the basis of terrain reference points. The analyses involved two stages. The first stage was an extensive study aimed at delineating forest areas separately from other surface cover types for both years. In the second stage we tried to analyze and assess the health conditions of forests of different species for the whole study area (intensive analyses). The results showed out that this methods of evaluating aerial photos can be used successfully to monitor the changes in covered area of different forest types, but it is less effective in health condition assessments. However, terrain observations must be made in both cases.